2014
DOI: 10.1002/chem.201405461
|View full text |Cite
|
Sign up to set email alerts
|

Dual Photo‐functionalized Amphiphile for Photo‐reversible Liquid Crystal Alignments

Abstract: Without the conventional polymer-based liquid crystal (LC) alignment process, a newly synthesized dual photo-functionalized amphiphile (abbreviated as ADMA1 ) was successfully applied as a robust photo-reversible LC alignment layer by self-assembly and photo-polymerization. The LC alignment layer constructed by directly adding dual photo-functionalized amphiphiles into LC media significantly cuts the manufacturing cost as well as opens new doors for the fabrication of novel electro-optical devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 30 publications
0
23
0
Order By: Relevance
“…The root‐mean‐square roughness of the nanosized continuous layer is about 2.87 nm (Figure d). Since the calculated geometric length of C 60 NS along the long axis was about 3.14 nm, this result indicated that nanosurfactant was assembled into monolayers, as additionally confirmed by water contact angle (WCA) measurements . The bare ITO‐coated substrate showed a WCA of 79.4°, whereas that of C 60 NS film equaled 96.8°, suggesting the formation of a hydrophobic layer (Figure S14, Supporting Information).…”
Section: Resultsmentioning
confidence: 66%
“…The root‐mean‐square roughness of the nanosized continuous layer is about 2.87 nm (Figure d). Since the calculated geometric length of C 60 NS along the long axis was about 3.14 nm, this result indicated that nanosurfactant was assembled into monolayers, as additionally confirmed by water contact angle (WCA) measurements . The bare ITO‐coated substrate showed a WCA of 79.4°, whereas that of C 60 NS film equaled 96.8°, suggesting the formation of a hydrophobic layer (Figure S14, Supporting Information).…”
Section: Resultsmentioning
confidence: 66%
“…If the LC can be prepared by chemically or physically connecting the photochromic group, these photochromic LC molecules can be applied to the remotely controllable materials [20]. The azobenzene chromophore can be transformed between two isomers with different absorption spectra induced by photoirradiation [21]. Thus, photoisomerisation from trans-to-cis and cis-to-trans of the azobenzene leads to changes in the electronic as well as the geometrical structure of the molecules [22].…”
Section: Introductionmentioning
confidence: 99%
“…For decades, reversible control of LC alignment has drawn particular attention as it plays a key role in the development of active switching components. It can be achieved by using an electrical field, a magnetic field, or light . Generally, LCs are always supported on functionalized solid surfaces or doped with functional materials to assist in realizing responses of LCs to external stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…It can be achieved by using an electrical field, [4] am agnetic field, [5] or light. [6][7][8][9][10][11][12][13][14][15] Generally,L Cs are always supportedo n functionalized solid surfaces [6][7][8][9][10]16] or doped with functional materials [17] to assist in realizing responses of LCs to external stimuli.R ecently,r eversible control of the alignment of LCs has also been reported at fluid interfaces. [18][19][20][21] For example, Kinsingere tal.…”
Section: Introductionmentioning
confidence: 99%